Extracellular Vesicles Play a Central Role in Cerebral Venous Disease‐Associated Brain Atrophy - Jia‐Yu Wang; Jing‐Ying Li; Dan Luo; Mei‐Ying Huang; Dong‐Hui Ao; Xin‐nan Liu; Xia Wang; Wei Ge; Yi‐Cheng Zhu (Advanced Science, 2023)
Abstract Cerebral venous abnormalities, distinct from traditional arterial diseases, have been linked to brain atrophy in a previous community‐based cohort study, specifically in relation to the reduction of deep medullary veins (r‐DMVs). To better understand the properties and biological functions of serum extracellular vesicles (EVs) in cerebral venous disease‐associated brain atrophy, EVs are extracted from the serum of both participants with r‐DMV and normal controls and analyzed their proteomic profiles using Tandem Mass Tag label quantitation analysis. Phenotypic experiments showed that EVs from individuals with r‐DMVs are able to disrupt the normal functions of neurons, endothelial cells, and smooth muscle cells, and induce A1 reactive astrocytes. Additionally, this study provided a comprehensive characterization of the proteomic profile of DMV EVs and found that the collagen hydroxyproline is upregulated, while complement C3 is downregulated in the r‐DMV group, suggesting that r‐DMV may not be a simple pathological phenomenon and highlighting the potential involvement of EVs in the progression of brain atrophy in r‐DMVs which has implications for the development of future therapeutic strategies.